Analisis good corporate governance terhadap pengungkapan ESG di Indonesia tahun 2016-2020 - Septiana, Woro Risma; Puspawati, Dewita (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of this study was to measure the effect of board size, women on the board, independent commissioners, remuneration committee, and audit quality on environmental, social, and governance (ESG) disclosures by companies in Indonesia. The ESG disclosure data used in this study comes from the Thomson Reuters database for a period of five years, from 2016-2020. The sampling method used was purposive sampling method, so that 39 sample companies were obtained for five years of observation (2016-2020) with 75 units of analysis. Data analysis used multiple linear regression analysis. Based on the results of the study, it can be concluded that independent commissioners and remuneration committees have an effect on ESG disclosure, while board size, women on the board and audit quality have no effect on ESG disclosure.